Development of Macromedia Flash Assisted Mathematics Learning Media on Straight Line Equations - Khairani, Putri (EduMatika: Jurnal MIPA, 2022)
The purpose of development research is to produce learning media using Macromedia Flash software on the material of Straight-Line Equations for SMP/MTs class VIII students. The development model used is ADDIE which has been modified, namely Analysis, Design and Development. The research subjects were students of MTs A – Jihad Medan class VIII using a small class scale of 10 people. The feasibility of learning media on the results of media assessment by experts on the developed learning media. Mathematics learning media using Macromedia Flash on the Straight-Line Equation material that was developed meets the criteria suitable for use for SMP / MTs class VIII students. The results of the material assessment by experts obtained 0.85 with a percentage of 85% and the criteria "Very Valid". The results of the material assessment by experts obtained 0.84 with a percentage of 84% and the criteria "Very Valid". The results of practicality with limited trials with students getting 0.87 with a percentage of 87% and the criteria of "Very Practical" so that the learning media is feasible and practical to use for learning SMP/MTs students